PENGGUNAAN MEDIA DART BOARD UNTUK MENINGKATKAN INGATAN MATERI BELAJAR BAHASA ARAB DI MTS ASSALAM MATARAM - Anggun Anabela Yustika Putri; Suparmanto Suparmanto; Muhammad Hasrul Sani; Muhammad Ittihadul Abidin (AL MA'ANY, 2023)
During earlier data observation on the study of arabic, some problems faced by students are found, that is teacher’s lack of learning media that results in student’s lack of motivation in learning and low achievement. Based on the problem found, the use of Dart Board Media is Applied. The purpose of this research is to find planning, process, and increase of students’ motivation and achievement. From the shown data results we can conclude that the use of dart board media can increase students’ motivation and learning achievement on learning the material arabic.